2015
DOI: 10.1088/1674-4527/15/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing motion types ofG-band bright points in the quiet Sun

Abstract: We study the motions of G-band bright points (GBPs) in the quiet Sun to obtain the characteristics of different motion types. A high resolution image sequence taken with the Hinode/Solar Optical Telescope (SOT) is used, and GBPs are automatically tracked by segmenting 3D evolutional structures in a space-time cube. After putting the GBPs that don't move during their lifetimes aside, the non-stationary GBPs are categorized into three types based on an index of motion type. Most GBPs that move in straight or nea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 37 publications
(81 reference statements)
3
28
0
Order By: Relevance
“…It implies that the majority of GBPs are jostled in a limited area, while the minority are pushed by granules far away. The proportion of stationary GBPs is higher than that reported by Bodnárová, Utz, and Rybák (2014) and Yang et al (2015a). They both indicated that there are about 50% stationary GBPs in a QS region.…”
Section: The Relation Between B P and Motion Rangementioning
confidence: 55%
See 4 more Smart Citations
“…It implies that the majority of GBPs are jostled in a limited area, while the minority are pushed by granules far away. The proportion of stationary GBPs is higher than that reported by Bodnárová, Utz, and Rybák (2014) and Yang et al (2015a). They both indicated that there are about 50% stationary GBPs in a QS region.…”
Section: The Relation Between B P and Motion Rangementioning
confidence: 55%
“…The different spatial samplings were overcome by bicubic interpolations of the NFI images obtaining adjusted NFI images with the spatial sampling of the Gband images. Next, the two time-series were aligned carefully by a high-accuracy solar image registration procedure based on a cross-correlation technique (Yang et al, 2015a): all G-band images in the time-series were aligned to its first image, and the NFI magnetograms were aligned to the G-band images according to the displacement between the simultaneous Stokes I image and the G-band image. To estimate the error of the stretched NFI magnetograms, we have performed the following experiment.…”
Section: Data and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations